Nutrients, Phytochemical, Antioxidant and Antimicrobial Analysis of Pterocarpus osun Stem Bark and Leaf for Their Nutritional, Medicinal Capacity - Fadeyi, Adewale Elijah; Adeniran, Oluremi Isola; Akiode, Saheed Olatunbosun (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Plants play a crucial role in human well-being and health. They provide some of the essential nutrients that humans require as well as act as medications to alleviate and cure various health problems. The purpose of this study is to look into the nutritional value, mineral composition, and the overall contributions of Pterocarpus osun to human nutrition and health. The result of the proximate analysis showed that protein is 9.52% in stem bark and 13.63% in the leaf, while the crude fiber in the stem bark is 37.89% and 46.03%, in the leaf. Ash, 6.74% and 7.46% in the stem bark and leaf respectively while carbohydrate content is 15.37% (stem bark) and 3.26% (leaf). Alkaloids, flavonoids, terpenoids, steroids, and tannins were detected in both organs of the plant tested. The mineral elements present include Ca, Mn, Fe, Ni, Mg, Zn, Cr, Co, Cd, Sulphur, and phosphorus. The antioxidant effect compared favorably well with that of the ascorbic acid used as standard. The extracts were screened for antimicrobial activities using eleven human pathogens. Each of the extracts successfully killed six microbes.